Metody pozyskiwania czytelnika w poradnikach intymnych, motywacyjnych i komputerowych - Ficek, Ewa (Stylistyka, 2021)
The basie topie of the considerations shown in the article are strategies subordinated to the impressive function, their essence being stimulating a reader’s attention, awakening a reader’s interest in the message and achieving the assumed therapeutic and didactic results. The research comprised positions that hit best the readers’ needs and are records of a specific type of communication and hence an interesting object oflinguistic observation - handbooks dealing with sexology (intimate handbooks), psychology (motivational handbooks) and computer science (computer handbooks). In the author’s opinion, the contents of a handbook can be - as a subjective act- a pretext for a sender to show himself; on the other hand, it is a medium through which an addressee can be subject to various stimuli (persuasive intentions: intra- and extra textual). The presented methods of gaining readers are manifested in distinct (and prevailing in the gathered materiał) tendencies to (I) make the reception of the message easy; (2) improve the communication of the message; and (3) expose the dialogue nature of the text, which is, in fact, a monologue.